RESULTS OF A STUDY OF THE INFLUENCE OF OIL CONTAMINATION ON WEAR OF THE WORKING SURFACE OF DIESEL CYLINDER LINES - Utaev, Sobir; Turaev, A (Scientific and Technical Journal of Namangan Institute of Engineering and Technology, 2023)
Objective: to study the influence of changes in the operational properties of oils and to monitor worn cylinder liners of D-243 diesel engines and transport tractors in order to determine the influence of the lubricating properties of motor oils on the wear of the working surface of cylinder liners.Methods: during the research, the laws of the theory of lubrication, wear friction, as well as methods based on existing regulatory documents were used.Results. When the engine is running, the oil, together with the contaminants in it, enters the annular grooves of the piston. This mixture, being in the piston grooves in the form of a thin film, at high temperatures, as a result of subsequent oxidative processes, forms viscous asphalt-resin deposits, which reduce the gaps in the grooves and, acting like slot filters, begin to retain contaminants. When operating diesel engines, cylinder liners are exposed to high temperature and pressure, as a result of which microroughness appears on the working surface under the influence of tribomechanical and tribotechnical influences. To determine the amount of wear on the working surface of engine cylinder liners, linear and weight methods, as well as the micrometer method, are widely used.Conclusion. Experience has shown that contaminants in motor oil consist of particles with a metal base and particles of organic compounds - varnish, similar in structure to graphite. When using diesel fuel with optimal concentrations, less varnish was formed, because wear is reduced to a lesser extent. During engine operation, as a result of natural wear of the liner, the uneven operation of the cylinders increases, performance characteristics decrease, and technical and operational indicators deteriorate. When operating diesel engines, cylinder liners are exposed to high temperature and pressure, as a result of which microroughness appears on the working surface under the influence of tribomechanical and tribotechnical influences. Micrometering of the liner must be carried out in different planes and sections, at least 10, which requires a long time.